The Implementation of Principle of Accuracy as a Test Stone for State Administrative Decisions - Mafruhah Mafruhah; Rr Herini Siti Aisyah; Farah Zhafirah Anindyaputri; Heru Irianto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Based on Article 53 of Law 9/2004, it is regulated that the basis for a lawsuit against the KTUN is the prevailing laws and regulations and the AUPB. In its development, Law 30/2014 was born which in Article 10 regulates the classification of the AUPB. One of the principles that have just been classified as AUPB in this provision is the principle of accuracy. In fact, this principle of accuracy has often been used as a touchstone by judges against a State Administrative Court. Based on this, the formulation of the problem in this article is First, the general principles of good governance as a touchstone for KTUN and Second, the application of the principle of accuracy as a test stone for KTUN. This research is legal research using statutory approach, conceptual approach, and the case approach. Based on the results of the research in this article, it was found that first, the classification of AUPB as a touchstone against KTUN, namely in the explanation of Article 53 paragraph (2) point b of Law 9/2004, AUPB which is specifically regulated in Law 30/2014, and, AUPB outside of Law 30/2014. As for the application of the Accuracy Principle as a Test Stone for KTUN, before Law 30/2014 came into effect, it had often been used as a test stone for KTUN, for example in the Kupang District Administrative Court Decision Number 5/G/2012/PTUN-KPG, Supreme Court Decision No. 150 K/TUN/1992, Supreme Court Decision No. 213 K/TUN/2007, Supreme Court Decision No. 101 K/TUN/2014, and Decision No. 02/G/2013 /PTUN JKT.